Effect of a focusing electric field on the formation of arc generated carbon nanotubes - Karmakar, Soumen; Nagar, Harshada; Pasricha, R.; Seth, T.; Sathe, V. G.; Bhoraskar, S. V.; Das, A. K. (Nanotechnology, 2006)
The effect of a focusing electric field on the formation of carbon nanotubes in a direct current arc-plasma is investigated. The hard deposits on the surface of the cathode are the main products, rich in multi-walled carbon nanotubes. It is seen that the focusing electric field has a distinct influence on the yield, purity and morphology of the nanotubes. The yield of the carbon nanotubes under the `focused field condition' has been found to be higher than that derived from the normal electrode configuration. It has been observed that the deposition of carbonaceous soot on the reactor wall is considerably reduced on application of the focusing electric field. Transmission electron microscopy has been used to determine the morphology of the nanotubes. In addition, Raman spectroscopy has helped in distinguishing the graphene-like structures from the disordered carbon networks and helped in analysing the morphology of the tubes. Thermal analysis gave a qualitative estimation of the relative yield of carbon nanotubes within the cathode deposits and their thermal stabilities. The crystalline nature of the samples has been confirmed by x-ray diffraction analysis. The results clearly indicate that the focusing electric field confines the positively charged carbon precursors within the cathode-anode space causing high relative yield and purity and has a distinct effect on controlling the inner diameter of the as-synthesized carbon nanotubes.

Surface studies on benzophenone doped PDMS microstructures fabricated using KrF excimer laser direct write lithography - Kant, Madhushree Bute; Shinde, Shashikant D.; Bodas, Dhananjay S.; Patil, K. R.; Sathe, V. G.; Adhi, K. P.; Gosavi, S. W. (Applied Surface Science, 2014)
his paper discusses microfabrication process for benzophenone doped polydimethylsiloxane (PDMS) using laser lithography. KrF excimer laser of 248 nm with 20 ns pulse width at repetition rate of 1 Hz was used for microfabrication of undoped and benzophenone doped PDMS. The doped-PDMS shows sensitivity below 365 nm, permitting processing under ambient light. The analysis of etch depth revealed that doped PDMS shows self developable sensitivity at lower fluence of similar to 250 mJ/cm(2). The unexposed and exposed surface was studied using Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), Raman spectroscopy and Scanning electron microscopy (SEM). Spectrocopic analysis indicated increase in C-O, C=O, Si-O-3 and Si-O-4 bonding at the expense of Si-C and Si-O-2 bonds of PDMS. In case of laser exposed doped-PDMS, removal of benzophenone from probe depth of spectroscopy was observed. Whereas the surface morphology of exposed and unexposed doped-PDMS was observed to be same, indicating clean development of PDMS micropattems. The present study indicates that addition of 3.0 wt.% benzophenone in PDMS enhance self development sensitivity of PDMS. The self developable results on doped-PDMS are quite encouraging for its potential use in point of care Lab-On-Chip applications, for fabricating micropattems using direct write laser lithography technology.
Keywords: Direct write laser lithography; Microfabrication; micropatterning; Poly(dimethylsiloxane) (PDMS)